Afrikaner identity in the born-free generation: Voortrekkers, farmers and Fokofpolisiekar - Loubser, Linda (My University, 2015)
The broad aim of this project is to examine the attitudes and opinions of the younger generation of Afrikaners born in or after 1994 at the birth of democracy in South Africa, also referred to as the ‘born-free’ generation, through the medium of long-form journalism. The project consists of two parts. The first is a theoretical and scholarly exploration of Afrikaner identity, including its history and how it is positioned in South Africa today. This is to highlight the baggage that the younger generation could be inheriting from the older generations, which have been described as suffering from a profound identity crisis since the advent of democracy in 1994. The research also examines some of the debates around Afrikaner identity that has played out in the media, as well as some of the writing about it. This includes debates around the Afrikaans language, as the language has been closely associated with Afrikaner identity from the outset. The second part of the project is a long-form article based on interviews with young Afrikaners. They were asked questions to probe how they see themselves in relation to the concept of an Afrikaner identity and how they see their place and future in South Africa. The article also contains elements of my own experiences as an Afrikaner and the issues around identity pertaining to that. While most of the research is not repeated in the long-form article, the article was informed by the theoretical and scholarly piece.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, in fulfilment of the requirements for the degree of Masters of Arts in Journalism and Media Studies. Johannesburg, September 2014